Knowledge management and information systems : strategies for growing organizations - Mellor, Robert B. (Basingstoke ; New York : Palgrave Macmillan, 2011)
"Knowledge Management and Information Systems Strategy for Growing Organizations examines the role that information systems play in helping SMEs use knowledge to achieve strategic organizational goals. Adopting a business perspective, it is ideal for students studying strategic information systems and knowledge management"--
Machine generated contents note: -- Introduction -- PART I: BACKGROUND -- Introduction to Knowledge Management -- Knowledge Management and Innovation -- Knowlege Management, Entrepreneurship and the Value Chain -- Information Systems and SMEs -- PART II: MODELLING THE THEORY -- Knowledge Valley Theory -- Managing Formal Knowledge -- PART III: APPLYING THEORETICAL PRINCIPLES -- Using Knowledge Valley Theory to Increase Organisational Innovation -- Factors that Stop Innovation -- Leadership and Innovation -- Knowledge and Learning -- PART IV: BUILDING APPLIED INFORMATION SYSTEMS -- Recombining Knowledge and Learning -- Drawing Conclusions -- PART V: THE PRACTITIONER VIEW -- Calculating the Benefit -- Larger Organisations -- Conclusion -- References -- Appendix -- Index.
Includes bibliographical references (p. 147-152) and index.
oif 12/09/14
Loan
Keywords: Knowledge management; Information resources management